2011
DOI: 10.1097/maj.0b013e31821a9d8e
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: A Disorder of Epithelial Cell Dysfunction

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by progressive dyspnea, interstitial infiltrates in lung parenchyma, and restriction on pulmonary function testing. IPF is the most common and severe of the idiopathic interstitial pneumonias (IIPs), with most individuals progressing to respiratory failure. Multiple lines of evidence reveal prominent roles for alveolar epithelial cells (AECs) in disease. Our current disease paradigm is that ongoing or repetitive injurious stimuli in the presence of a genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…The mechanisms by which telomere defects provoke lung disease are not understood, but a number of observations have pointed to lung-intrinsic factors and epithelial dysfunction as candidate events (6)(7)(8)(9)(10). For example, in telomerase-null mice, DNA damage preferentially accumulates in the air-exposed epithelium after environmentally induced injury, such as with cigarette smoke (7).…”
mentioning
confidence: 99%
“…The mechanisms by which telomere defects provoke lung disease are not understood, but a number of observations have pointed to lung-intrinsic factors and epithelial dysfunction as candidate events (6)(7)(8)(9)(10). For example, in telomerase-null mice, DNA damage preferentially accumulates in the air-exposed epithelium after environmentally induced injury, such as with cigarette smoke (7).…”
mentioning
confidence: 99%
“…Emerging evidence suggests that repetitive epithelial injury contributes to IPF (35). Repetitive epithelial injury, as caused by the combination of neonatal hyperoxia and influenza A virus or neonatal hyperoxia and bleomycin, may be a common feature in our two models.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with idiopathic pulmonary fibrosis (IPF) present with breathlessness on exertion, dry cough, subpleural honeycombing on high-resolution computed tomography, and the presence of hyperplastic epithelial cells overlying organized myofibroblasts in biopsies (35). Because these lesions are often patchy, lacking inflammation, and refractory to conventional anti-inflammatory strategies, the concept that IPF is an inflammatory-mediated lung disease has now shifted to considering it a disease of repetitive epithelial injury with impaired repair.…”
Section: Discussionmentioning
confidence: 99%
“…Unresolved injury-induced impaired proliferative capacity and an increased apoptotic rate of AECs represents potentially important mechanisms in the development of lung fibrosis (4,5). Failed epithelium repair is followed by abnormal wound healing processes, including epithelial and fibroblast activation, cytokine production, coagulation pathway activation, neoangiogenesis, re-epithelialization and fibrosis (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only lung transplantation has been proved to be effective in the treatment of IPF, due to its poorly understood etiology and pathogenesis (1,2). Increasing evidence has demonstrated that recurrent or continuous injury to the lung epithelium initiates and promotes lung fibrosis (3,4). Unresolved injury can lead to compromised proliferative capacity of the alveolar epithelial cells (AECs), increased cell death (either necrosis or apoptosis), and a phenotypic switch of the surviving cells (5,6).…”
Section: Introductionmentioning
confidence: 99%